Análise gráfica do cavaco obtido no torneamento com diferentes geometrias de ferramenta e parâmetros de corte - Silva, Gabriel Augusto da (Universidade Federal de São Carlos, 2025)
Due to the geometry of the tool-chip contact area, non-uniform stresses occur in different regions of the tool. A better understanding of them is essential for determining the tool geometry and adequately adjusting the cutting parameters. Characterizing this contact through the geometric analysis of the chip is an efficient way of knowing the acting forces. Thus, this work aims to obtain, through computer-aided modeling (CAD), the geometry of chips obtained from different conditions, with variation in feed, nose radius and edge radius. With the chip thicknesses along the contact length and their respective area, it was possible to determine the specific cutting force and total cutting force by applying the equation proposed by Kienzle. As expected, the analyses showed that increasing the feed and decreasing the nose radius lead to an increase in chip thickness in general terms, causing a decrease in the specific cutting force. Furthermore, increasing the cutting edge radius and increasing the feed lead to an increase in the contact area between the tool and the chip, as well as an increase in the cutting force.
Graphical analysis of the chip obtained in turning with different tool geometries and cutting parameters
Keywords: Usinagem; CAD; Modelo geométrico; Força de corte; Machining; Geometric model; Cutting force; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO